Chapter 1 The challenges of expansion and democratization of education A historical look at school exclusion in Haiti - Etienne, Jean Fritzner (Taylor & Francis, 2023)
The history of public education in Haiti has been characterized by an idealistic notion of extending the enlightenment of education throughout the country. This notion is reflected in the establishment of an important legal arsenal which, since the 19th century, has defined three main principles of the Haitian school system. These three principles have been a constant throughout the history of the country. They were intended to promote the expansion and democratization of schools in Haiti. Overshadowed by academic liberalism, the principles of free and compulsory education remain, however, merely an illusion for the majority of the country's children. Despite pompous speeches from its political leaders, Haiti has failed to catch up with the expansion and democratization of schools. Its educational system faces many challenges, including the problem of access to school, the lack of physical infrastructure and the shortage of qualified teaching staff. These challenges have extended the exclusion and inequality which stem from the contempt of the Haitian elites for the education of the people, in particular those in the countryside, and in an economic model based on food, not industry.